Fine Root Seasonal Dynamics, Plasticity, and Mycorrhization in 2 Coexisting Mediterranean Oaks with Contrasting Aboveground Phenology - Coll, Lluís; Camarero, Araid; Aragón, Juan Martínez De; Camarero, Jesús Julio; Martínez de Aragón, Juan; Camarero, Araid; Aragón, Juan Martínez De (Ecoscience, 2012)
To advance understanding of the mechanisms underpinning the coexistence of Mediterranean oak species, we conducted a year-long analysis of the production, architecture, and mycorrhization status of the fine roots of a mixed evergreen (Quercus ilex) and winter deciduous (Quercus faginea) oak stand. We used the ingrowth bag technique to sample the fine roots produced by each species in spring, summer, and winter. For each season, root architecture traits (specific root length, root diameter, root tips) and variables associated to root ectomycorrhizal status were measured in the laboratory. Results showed a marked seasonality in the fine root architecture, including more fine root tips and longer roots per unit of weight formed in spring and summer, revealing a capacity in Mediterranean oak species to modify root architecture in spring and suggesting the possibility of increased resource capture in summer. Fine root ectomycorrhizal status was comparable between species and also showed marked seasonality: we found a high percentage of roots colonized by dead ectomycorrhizas in winter but low ectomycorrhizal colonization rates in summer. Quercus ilex produced greater amounts of fine roots than Q. faginea (particularly during spring), suggesting greater competitive ability in the former species for belowground resources.
Keywords: architecture et le statut; Chênes; coexistence d; des mécanismes supportant la; Ectomycorrhizae; espèces méditerranéennes de; et caduques; feuilles persistantes; fine roots; l; mixte de chênes à; mycorhizien des radicelles d; nous avons analysé sur; nous avons utilisé la; Phenology; pour accroître notre compréhension; Quercus faginea; Quercus ilex; résumé; root traits; technique du sac; un peuplement; une année la production